Data gathering problem with the data importance consideration in Underwater Wireless Sensor Networks. (15th January 2017) - Cheng, Chien-Fu; Li, Lung-Hao
Abstract: In Underwater Wireless Sensor Networks (UWSNs), if sensors rely on multi-hop transmission to send sensing data to the sink above the water, sensors that are closer to the water's surface will deplete energy sooner because they share a larger load of the packet relaying work. This problem becomes worse if the water being monitored is very deep. This imbalance in energy consumption can be effectively mitigated by using an Autonomous Underwater Vehicle (AUV) to collect data. However, if the data to collect are important, the delay time required by this data gathering method may be too long. In this study, we integrate the two data gathering mechanisms mentioned above, namely utilization of AUVs and multi-hop transmission, to reduce the problem of unbalanced energy consumption and long delay time. Moreover, we also investigate how to determine the importance level of data and set delay time requirements without domain knowledge. Our purpose is to deliver data of higher importance to the sink within the delay time requirement. Our experimental results confirm that the proposed method can effectively mitigate the imbalance in energy consumption, reduce the delay time required for delivering important data, and also prolong the network lifetime.